Financiamiento de proyectos de vivienda con métodos de alternativos (2018)
The main reason why this research is done is to find a new sustainable system to finance housing projects, to transform the financial cost generated by a bank loan to the client, towards more benefits so that in this way they can help them acquire their home, and in turn to the construction companies to help them finance their projects or, if necessary, to reduce the percentage that is requested in the bank loan and, why not, to finance 100% of the projects with a new system.